KONTRIBUSI PENGUASAAN UNSUR INTRINSIK TEKS CERPEN TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA NEGERI 2 BUKITTINGGI - Sandri, Yunita; Hafrison, Mhd. (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This article reveals the contribution of mastery of the intrinsic elements to writing skills of the short story text grade students XI SMAN 2 Bukittinggi. The purpose of this research there are three. First, it describes the mastery of the intrinsic elements. Second, it describes the writing skills of the short story text. Third, describing the contribution of mastery of the intrinsic elements to writing skills of the short story text. This research type is quantitative, descriptive method, and design contribution. This research population is grade XI that are registered on the school year 2018/2019, i.e. as many as 311 students. The sample in this research are determined by proportional random sampling of 10% of the population, i.e. 30 students. The research data are scores as a result of mastering the intrinsic elements and the scores of writing skills from the short story text. The data obtained through two types of tests i.e. objective tests to measure the mastery of the instrinsic elements and performance tests to measure the skills of writing a short story text. The results of the research there are three. First, the mastery of the intrinsic elements are on good qualifications (B) by the value of the average 77,67. Second, the skills of writing text short story are on more than enough qualifications (LdC) with an average of 70,00. Third, there is a contribution of the intrinsic elements to writing skills of the short story text grade students XI SMAN 2 Bukittinggi at 66,26%. Kata kunci: Kontribusi, Penguasaan, Unsur Intrinsik, Keterampilan, Menulis, Teks Cerpen